2018
DOI: 10.1037/xhp0000572
|View full text |Cite
|
Sign up to set email alerts
|

The effects of attention and adaptation duration on the motion aftereffect.

Abstract: The motion aftereffect (MAE) is the perception of illusory motion following extended exposure to a moving stimulus. The MAE has been used to probe the role of attention in motion processing. Many studies have reported that MAEs are reduced if attention is diverted from the adaptation stimulus, but others have argued that motion adaptation is independent of attention. We explored several factors that might modulate the attention-adaptation relationship and therefore explain apparent inconsistencies, namely (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…Consistent with our previous research (Bartlett et al, 2018), adaptation duration did not significantly moderate attentional modulation of the MAE. Previously we examined whether attention affects the rate at which the MAE builds up, or the asymptotic MAE.…”
Section: Nonsignificant Moderatorssupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with our previous research (Bartlett et al, 2018), adaptation duration did not significantly moderate attentional modulation of the MAE. Previously we examined whether attention affects the rate at which the MAE builds up, or the asymptotic MAE.…”
Section: Nonsignificant Moderatorssupporting
confidence: 92%
“…Prior work has demonstrated that MAEs increase with adaptation duration (e.g. Bartlett et al, 2018). As discussed above, this duration-related increase in MAEs is not associated with increased attentional modulation.…”
Section: Nonsignificant Moderatorsmentioning
confidence: 68%
See 1 more Smart Citation
“…Especially, contradictory results have been found regarding the role of attention and distraction on some types of visual adaptation. For example, some studies have shown that attention load failed to modulate the motion aftereffects (e.g., Morgan, 2011 , 2012 , 2013 ; Morgan and Solomon, 2019 ); however, other studies have showed that a high-attention load during adaptation decreased the strength of the motion aftereffects (e.g., Chaudhuri, 1990 ; Rees et al, 1997 ; Taya et al, 2009 ; Bartlett et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the neural level, adaptation is reflected in shifts in the firing rates of cells in response to prolonged exposure to a constant stimulus. Such effects have been observed across a variety of stimulus properties, including motion (Addams, 1834;Bartlett et al, 2018), light intensity, and orientation (Carandini et al, 1998;Dragoi et al, 2000;Gutnisky & Dragoi, 2008;Müller et al, 1999), and in both human and non-human animals (Howard et al, 1987;Laughlin, 1989;Shapley & Enroth-Cugell, 1984).…”
Section: Introductionmentioning
confidence: 99%